Islamic Juridical Solutions for the Housing Shortage: A Juridical and Economic Study (Iraq as a sample) - Miqdad Haidar, Warqaa (International Journal of Psychosocial Rehabilitation, 2020)
Our glorious Sharia, from its jurisprudential perspective, which seeks to achieve the objectives of the Sharia, is concerned with important human issues, preserving religion, soul, honor, reason, and money, so the research study came to deal with how to deal with the housing crisis by presenting jurisprudential opinions and proposing legal alternatives from a jurisprudential and economic perspective. Life, including housing, is the environment in which a person lives, protects himself from the cruelty of nature, and preserves his dignity, and in order to get rid of the burdens of loans that burden the citizen looking for housing and from the high rents and interest in real estate banks and other things, the search for legitimate alternatives to these obstacles is a legal and social necessity, so this research came to contribute to presenting these alternatives through its discussion: - It dealt with the concept of housing loans and its most important caveats in the exacerbation of the housing crisis and dealt with the concept of housing loans and its most important caveats in the exacerbation of the housing crisis.